The investigation of the electrical properties of a newly synthesized phthalocyanine thin film and the effect of the preparation conditions - Aktaş, Yasemin; Şen, Pınar; Dumludağ, Fatih; Altındal, Ahmet; Özer, Metin; Bulut, Mustafa; Bekaroğlu, Özer (My University, 2008)
A detailed study of the effect of the film preparation conditions on the d.c and a.c conductivity of a newly synthesized trinuclear phthalocyanine (CuPc) thin film was investigated. Thin films have been prepared by different methods (seamering and airbrush) at different substrate temperatures and derivative were carried out at the temperatures between 290 K and 420 K. We find that the experimental data are described by thermally activated conductivity dependence on temperature. The frequency dependence of the conductivity follow a universal power law ‘ωs ’ for all compounds. The comparison of the experimentally determined s values and the temperature dependence of the ac conductivity with the prediction of CBH model suggest that the obtained results are in agreement with the prediction of the CBH model for all films.
Keywords: Phthalocyanine; Activation energy; Correlated barrier hopping